Stability of volatile sulfur compounds (VSCs) in sampling bags - impact of temperature - Le, H (Water science and technology : a journal of the International Association on Water Pollution Research, 2013)
Volatile sulfur compounds (VSCs) are a major component of odorous emissions that can cause annoyance to local populations surrounding wastewater, waste management and agricultural practices. Odour collection and storage using sample bags can result in VSC losses due to sorption and leakage. Stability within 72 hour storage of VSC samples in three sampling bag materials (Tedlar, Mylar, Nalophan) was studied at three temperatures: 5, 20, and 30 °C. The VSC samples consisted of hydrogen sulfide (H2S), methanethiol (MeSH), ethanethiol (EtSH), dimethyl sulfide (DMS), tert-butanethiol (t-BuSH), ethylmethyl sulfide (EMS), 1-butanethiol (1-BuSH), dimethyl disulfide (DMDS), diethyl disulfide (DEDS), and dimethyl trisulfide (DMTS). The results for H2S showed that higher loss trend was clearly observed (46-50% at 24 hours) at 30 °C compared to the loss at 5 °C or 20 °C (of up to 27% at 24 hours) in all three bag materials. The same phenomenon was obtained for other thiols with the relative recoveries after a 24 hour period of 76-78% at 30 °C and 80-93% at 5 and 20 °C for MeSH; 77-80% at 30 °C and 79-95% at 5 and 20 °C for EtSH; 87-89% at 30 °C and 82-98% at 5 and 20 °C for t-BuSH; 61-73% at 30 °C and 76-98% at 5 and 20 °C for 1-BuSH. Results for other sulfides and disulfides (DMS, EMS, DMDS, DEDS) indicated stable relative recoveries with little dependency on temperature (83-103% after 24 hours). DMTS had clear loss trends (with relative recoveries of 74-87% in the three bag types after 24 hours) but showed minor differences in relative recoveries at 5, 20, and 30 °C